2011
DOI: 10.1111/j.1740-0929.2011.00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring polymorphisms and their effects on reproductive traits of the INHA and INHβA genes in three goat breeds

Abstract: In this study, we report the analysis of INHA and INHβA gene polymorphisms in 786 goats of three breeds: Xinong Saanen (SN), Guanzhong (GZ) and Boer (BG). We identified three new allelic variants: P1-C80G and/126G (GenBank accession no. HQ202573) in the three goat breeds and P2-C936T (GenBank accession no. HQ202572) in SN and GZ goat breeds. At P1 locus, AA, AB and BB genotypes were found in the three goat breeds. At P2 locus, CC and CT genotypes were found in SN and GZ goat breeds. After comparing genotype di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Overall, the highest coverage by ROH was observed on chromosome 1, 2, 6 respectively. Gene INHA, located on chromosome 2, was reported as a candidate gene for litter size in goats [24]. The PPP1R36 and Heat Shock Protein A2 (HSPA2) (CHI10, 26.402-26.719 Mb) identi ed in this communal indigenous goats are involved in heat stress response and in other studies, HSPA2, DNAJC24, and DNAJC13 are associated with the heat shock family of genes [55] .…”
Section: Discussionmentioning
confidence: 76%
“…Overall, the highest coverage by ROH was observed on chromosome 1, 2, 6 respectively. Gene INHA, located on chromosome 2, was reported as a candidate gene for litter size in goats [24]. The PPP1R36 and Heat Shock Protein A2 (HSPA2) (CHI10, 26.402-26.719 Mb) identi ed in this communal indigenous goats are involved in heat stress response and in other studies, HSPA2, DNAJC24, and DNAJC13 are associated with the heat shock family of genes [55] .…”
Section: Discussionmentioning
confidence: 76%
“…Chu et al (2007) identified 21 new SNPs of INHβA that significantly influenced litter size in Small Tail Han sheep. Furthermore, Hou et al (2012) identified a synonymous mutation, C936T, of INHβA in three goat breeds, but a functional analysis revealed that this mutation had no effects on its biological function and was not associated with litter size. To date, no significant association of INHβA polymorphisms with female reproductive traits have been identified in bovines.…”
Section: Discussionmentioning
confidence: 99%
“…Chu et al (2007) identified 21 single nucleotide polymorphisms (SNPs) of INHβA, which significantly influenced litter size in Small Tail Han sheep. Hou et al (2012) detected one SNP, C936T, of INHβA in Xinong Saanen, Guanzhong, and Boer goats, but did not show statistically significant associations with litter size. To date, no significant association of INHβA polymorphisms with female reproductive traits has been revealed in bovines.…”
Section: Introductionmentioning
confidence: 99%
“…In goat, the studies worked to identify the key genes that involved in the regulation of ovulation rate and kidding rate by transcriptome sequencing of goat ovaries, and the signaling pathways that affected ovulation and fertility [1,4,[19][20][21][22][23][24][25]. The study on litter size of goats showed that PDGFRB, MARCH1, KDM6A, CSN1S1, SIRT3, KITLG, GHR, ATBF1, INHA, GNRH1 and GDF9 might be candidate genes for goat reproductive traits [22,[26][27][28][29][30][31][32][33][34][35]. Growth hormone (GH) and members of the insulin-like growth factors (IGF-I and IGF-II) family system may play a key role in the follicular development and atresia [2,36], and the genes FER1L4 and SRD5A2 may be associated with the high fecundity of goats [37].…”
Section: Introductionmentioning
confidence: 99%